Análisis de la gestión documental en la secretaría de la Unidad Educativa Carlos Alberto Aguirre Avilés de la Parroquia La Unión - Flores Cavero, Lilibeth Vanessa (2020)
The present case study whose theme is "Analysis of the document management of the secretariat of the Carlos Alberto Aguirre Avilés Educational Unit of La Unión Parish." which was done to evaluate many problems that existed within the secretariat department, which caused many disagreements for parents, teachers and students. To detect the problems, a diagnosis was made within the institution's secretariat department, such as the documentation of the department, which is of utmost importance in order to carry out student procedures; For this, a computer was needed to be able to save the information and thus be able to have backup of all procedures that are carried out within the department, the space of the department was very limited to better organize the filing cabinets; The delay in delivering the required documentation is another important point, since many times there were days late when delivering a document that had been requested days in advance and especially the opinion of parents, teachers and students who felt dissatisfied With the type of service that was provided, this was done in order to be able to look for possible and future solutions so that there are no longer disagreements within the department. All this arose within the department was due to the lack of administrative personnel who sometimes left their jobs to attend meetings that were organized by the rector of the institution; then no one was left in charge of the place during the absence of the secretary. This Institution is located in the Province of Los Ríos Cantón Babahoyo Parroquia La Unión.